1991
DOI: 10.1177/0883073891006002081
|View full text |Cite
|
Sign up to set email alerts
|

Vigabatrin in Pediatric Epilepsy—An Open Study

Abstract: The antiepileptic effect of vigabatrin in adults has been demonstrated in a number of controlled studies. In children, the effect of vigabatrin has been investigated only to a limited extent. In order to assess the long-term effect and safety of vigabatrin in patients with severe epilepsy, an open, add-on, dose-ranging study was initiated. To date, 27 children with partial epilepsy, two with generalized epilepsy, two with Lennox-Gastaut syndrome, and one with nonclassifiable epilepsy have been enrolled in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…A further open study of 33 patients reported aggression in 9.1 % and hyperkinesia in 6.1% of children treated with vigabatrin. The majority continued on vigabatrin (47). The overall incidence of behavioural disturbances in these studies was 14.2%.…”
Section: Reports Of Severe Behavioural Disturbances In Children Treatmentioning
confidence: 65%
See 1 more Smart Citation
“…A further open study of 33 patients reported aggression in 9.1 % and hyperkinesia in 6.1% of children treated with vigabatrin. The majority continued on vigabatrin (47). The overall incidence of behavioural disturbances in these studies was 14.2%.…”
Section: Reports Of Severe Behavioural Disturbances In Children Treatmentioning
confidence: 65%
“…In contrast, Sander et al (8) reported a single patient who developed a schizo-manic reaction after 32 weeks of therapy and another patient who developed aggressive outbursts after 6 months of treatment. The studies in children considered earlier (44)(45)(46)(47) included long-term follow-up data, but the timing of adverse events was generally not given. However, the impression is that they tended to occur early in treatment.…”
Section: Timing Of Reactionsmentioning
confidence: 99%
“…Vigabatrin was found to be most effective in partial seizures, but no clear dose-response relationship was found. An open-labelled, add-on study (Uldall et al 1991) in 33 children with epilepsy found a >50% reduction of seizures in 54% of patients, with 21 % being seizure free . However, seizures recurred in some patients, which may have been related to the reduction in number or dosage of concomitant drugs.…”
Section: Paediatric Usementioning
confidence: 98%
“…Vigabatrin (γ-vinyl-GABA) is an antiepileptic drug successful in the management of childhood seizures including infantile spasms [1][2][3][4][5][6][7]. The anticonvulsant effect of vigabatrin is achieved by irreversible inhibition of the enzyme GABA-transaminase used to break down the inhibitory neurotransmitter GABA.…”
Section: Introductionmentioning
confidence: 99%